Les politiques agricoles de l'Indonésie et de la Malaisie face aux impératifs de la sécurité alimentaire - Stéphane Bernard; Jean-François Bissonnette (VertigO)
Since the 1960s, most Southeast Asian countries have managed to reach greater food security, largely by focusing on output increase. The postcolonial state was instrumental in improving agricultural production in Indonesia and Malaysia; however the state policies have been changing especially since the turn of the millennium. In order to address the transformations which have taken place in contemporary agricultural policies in those states, we ask the following question: What are the strategies deployed by Indonesian and Malaysian states to insure food security? To answer this question, policies pertaining to the two most important agricultural sectors in both countries, rice and palm oil, are analysed. Both states have pursued policies of self-sufficiency in regards with rice production. Despite the adoption of liberalization policies since the end of the 1990s in both countries, many mechanisms ensure the regulation of the rice economy. In parallel, Malaysian and Indonesian administrations have been aiming to significantly expand cash crop production, especially oil palm. In both cases, the state played a key role in the development of palm oil production while supporting smallholdings. However, as states have encouraged cash crop production for exports, earlier objectives of food self-sufficiency have been abandoned to a large extent. Relinquishing food self-sufficiency as a priority appears risky especially in Indonesia where a large part of the population in rural and urban remains food insecure.